DIAGNOSTIC SIGNIFICANCE OF ADENOSINE DEAMINASE IN PLEURAL TUBERCULOSIS - Khurshid, Rukhshan; Shore, Najla; Saleem, Mahjabeen; Naz, Mammona; Zameer, Nazia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Tuberculosis (TB) is a major cause of pleural effusion, which in TB usually has lymphocytic and exudative characteristics. Analysis of adenosine deaminase (ADA) activity is a very useful diagnostic approach to achieve a more rapid and precise diagnosis in cases of Pleural TB (pTB). Methods: Fifty male and fifty female patients presenting with tuberculous pleural effusion was included in the study. The patients were taken from the medical ward of Sir Ganga Ram Hospital between September 2001 and September 2002. Activity of Adenosine Deaminase (ADA) was estimated by the technique of Sodium dodecyl sulphate electrophoresis (SDS-EF) using 10% polyacrylamide gel. Results: Mean age of males was 45.72±19.22 years and of female was 43.74±16.09 years. Mean protein level was 3.39±0.24 g/dl in males, and it was 3.02±0.26 g/dl in females. Mean specific gravity both in males and females was 1.020±0.01. The results show an increased level of enzyme ADA in patients as compared to normal subjects. Conclusion: Estimation of ADA activity may provide basis for rapid and efficient diagnosis of pleural TB in different clinical settings. However study should be extended to larger number of patients to reach a better conclusion. Keywords: Adenosine deaminase, Pleural TB, Electrophoresis